RELATIONSHIP BETWEEN FAMILY SUPPORT AND MEDICAL COMPLIANCE IN PATIENTS WITH PULMONARY TUBERCULOSIS IN THE WORKING AREA OF THE COMMUNITY HEALTH CENTER OF ABELI, KENDARI - Mongan, Ruth; Fajar, Fajar (YCAB Publisher & IAKMI SULTRA, 2017)
Background: Little is known about the relationship between family support (emotional, material, and informational support) with medical compliance in tuberculosis patients in the Community Health Center of Abeli KendariObjective: This study aims to examine the relationships of family support (emotional, material, and informational support) and medical compliance of patients with pulmonary tuberculosis.Methods: This was an observational study with cross-sectional design. Thirty samples were recruited by total sampling with the criteria that they had pulmonary TB with positive acid-resistant bacteria and still taking medication from the community health center of Abeli Kendari health center. Data were analyzed by chi-square processed using univariate and bivariate and presented in tabular form and narrated.Results: Findings showed that there were significant relationship between Emotional support (X2hit = 10.20 > the value of X2tab = 3.841; Cc 0.50 - moderate relationship ), material support (X2hit = 6.00 > the value of X2tab = 3.841; Cc 0.41 - moderate relationship), and informational support (X2hit = 13.50 > the value of X2tab = 3.841; Cc 0.56 – strong relationship) with p-value < 0.05.Conclusion: there was a significant relationship between family support (emotional, material, and informational support) with medical compliance of patients with pulmonary tuberculosis. It is suggested for health professionals to always promote the importance of family support for the successful of medical treatment among tuberculosis patients.